Endotelijski hiperpolarizirajoči dejavnik in mikrocirkulacija kože - Lenasi, Helena (Medicinski razgledi, 2008)
The skin microcirculation is controlled by systemic and local factors; the latter are mainly released from the endothelium. One of important endothelial vasodilators is endothelium-derived hyperpolarizing factor (EDHF) whose function can be assessed by blocking ocher vasodilators, such as nitric oxide (NO) and prostacyclin (PGIZ). The role and nature of EDHF in humans remains tobe elucidated. The aim of our study was therefore to investigate and characterize the NO- and PGhindependent mechanism, potentially attributable toEDHF, in human skin microcirculation. 14 healthy male volunteers (aged 20 to37 years, mean age 25.9 +- 1.7) were included in the study. Cutaneous blood flow was measured using the laser Doppler (LD) method on the volar aspect of the forearm and expressed in perfusion units (PU). Endothelial nitric oxide synthase (eNOS) and cyclooxygenase (COX) were inhibited by subcutaneously injecting N°'-monomethyl L-arginine (L-NMMA) and diclofenac, respectively. Thepotential involvement of cytochrome P450 (CYP) in the generation of EDHF was evaluated by injecting the selective CYP 2C9 inhibitor sulfaphenazole. Thebaseline LD flow and microvascular reactivity were assessed by performing iontophoresis of acetylcholine (ACh, endothelium-dependent vasodilator) and bymeasuring postocclusive reactive hyperemia (PRH). eNOS and COX inhibition did not affect the baseline LDF (12.5 +- 2.3 PU in the treated site and 10.9 +- 1.8 PU in the control site, t-test), but it significantly attenuated ACh-induced vasodilatation in the eNOS and COX-treated site (35.6+-5.7PU in the treated site vs. 66.6 +- 8.3 PU in the control site, t-test, p < 0.05). (Abstract truncated at 2000 characters)
Keywords: Endotelij žilni; Skin; Koža; Blood Supply; Microcirculation; Mikrocirkulacija; Laser-Doppler Flowmetry; Vazodilatacija; Laser-dopplersko merjenje hitrosti pretoka; Endothelium, Vascular; Citokrom P-450; Vasodilation; Prostaglandini; Adult; Cyclooxygenase Inhibitors; Diklofenak; Dušikov-oksid, sintaza; Diclofenac; Nitric-Oxide Synthase; Odrasli; Antagonists And Inhibitors; Ciklooksigenazni inhibitorji; Ionofori; Ionophores; prekrvavitev; Prostaglandins; žilni endotelij; Cytochrome P-450